Essays about digital innovation on consumer behavior - Fang, Sihan (Nanyang Technological University, 2024)
In the first chapter, I explore the impact of video streaming platforms on offline movie consumption. The subscription-based business model is disruptive in the copy-right industries. More than a digitalized distribution channel, it fundamentally transforms both the supply and demand sides by offering new forms of content creation, provision, and consumption. However, the effects of these business models on the local offline industry are less well-understood, especially in the case of the motion picture industry. This study investigates the impact of the subscription-based business model on offline activity consumption in the motion picture industry. Leveraging a unique dataset with individuals’ every transaction record and a difference-in-differences approach, this study shows that Netflix subscription interestingly increases offline movie consumption. Based on the argument that individuals have unmet social and hedonic demands that are imperfectly met by subscription-based services like Netflix, this study shows that offline movie consumption actually increases post-subscription, accompanied by social and hedonic activities like dining and entertainment spending. This study also provides evidence that the identified effect on offline movie consumption is more pronounced for individuals with higher social (i.e., lower-income people) and hedonic (i.e., younger people) needs. This work provides clear implications for managers and policymakers who are involved in both subscription-based platforms like Netflix and the traditional offline movie industry. In addition, this study provides theoretical implications for the study of subscription-based platforms, imperfect substitution of channels, and the role of social and hedonic value in technology-supported platforms.